Interaksi Pembaca dan Narasi Interaktif dalam Sastra Digital: Kajian Resepsi pada Aplikasi Webnovel - Alpan Ahmadi; Wahidatul Murtafiah (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
The transformation of literature from print to digital platforms has altered the ontology of texts and the position of the reader. The Webnovel application introduces real-time interactivity features, such as paragraph-level comments and voting systems, allowing readers to participate directly in the storytelling process. This study aims to analyze the forms of reader interaction and how such interactivity influences narrative construction in digital literature through the lens of reception aesthetics. This study employs a qualitative approach with digital ethnography. Research data, consisting of reader comments and narrative fragments, were purposively sampled from popular ongoing works on the Webnovel app. Analysis was conducted by applying Wolfgang Iser's reception theory, specifically the concept of